2017
DOI: 10.1099/jgv.0.000723
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral activity of acid beta-glucosidase 1 on enterovirus 71, a causative agent of hand, foot and mouth disease

Abstract: Enterovirus 71 (EV71) is a causative agent of hand, foot and mouth disease (HFMD). EV71 causes fever, rash, diarrhoea and, in some cases, acute encephalopathy/encephalitis, which can be fatal. No specific treatment is currently available for EV71 infection. Here, we conducted a cDNA library screen and identified acid b-glucosidase 1 (GBA1; also known as bglucocerebrosidase) as an EV71 resistance factor. The anti-EV71 function of GBA1 was verified by gene transduction and knockdown experiments. Cerezyme, a mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Previous in vitro studies demonstrated that hSCARB2 binds β-GC at pH 6.5, whereas it does not at pH 5.5 ( Zhao et al, 2014 ). Interestingly, the binding site(s) of hSCARB2 for β-GC [amino acids 145-222 ( Zachos et al, 2012 ) or 150–167 ( Reczek et al, 2007 )] overlaps with the binding site(s) for EV71 [amino acids 142-204 ( Yamayoshi and Koike, 2011 ) or 144–151 ( Chen et al, 2012 )], and exogenous β-GC has been found to interfere with EV71 binding to hSCARB2 on the cell surface ( Nakata et al, 2017 ). This implies that release of β-GC from hSCARB2 at pH 5.5 may enhance the interaction between EV71 and hSCARB2, thus boosting EV71 uncoating.…”
Section: Discussionmentioning
confidence: 99%
“…Previous in vitro studies demonstrated that hSCARB2 binds β-GC at pH 6.5, whereas it does not at pH 5.5 ( Zhao et al, 2014 ). Interestingly, the binding site(s) of hSCARB2 for β-GC [amino acids 145-222 ( Zachos et al, 2012 ) or 150–167 ( Reczek et al, 2007 )] overlaps with the binding site(s) for EV71 [amino acids 142-204 ( Yamayoshi and Koike, 2011 ) or 144–151 ( Chen et al, 2012 )], and exogenous β-GC has been found to interfere with EV71 binding to hSCARB2 on the cell surface ( Nakata et al, 2017 ). This implies that release of β-GC from hSCARB2 at pH 5.5 may enhance the interaction between EV71 and hSCARB2, thus boosting EV71 uncoating.…”
Section: Discussionmentioning
confidence: 99%
“…EV71 infection is strongly associated with severe HFMD, which is accompanied by neurological symptoms and usually leads to death. Therefore, many studies have focused on the identification of substances with activity against EV71, and these studies have identified many candidate drugs for the treatment of EV71 infection, such as amphotericin B, isochlorogenic acid C, acid beta‐glucosidase 1, sulfated rhamnan, and suramin . Considering their relatively low cytotoxicity, extracts from traditional Chinese medicines or foods show particular advantages and have attracted increasing attention …”
Section: Discussionmentioning
confidence: 99%
“…For instance, SCARB2 was identified as a receptor for EV71 by Yamayoshi et al [50]. Nakata et al [51] later reported that acid beta-glucosidase 1 (GAB1) restricts EV71 infections by interacting with SCARB2 and reducing its expression on the cell surface. Further, it was shown that recombinant human GBA1, a drug originally used to treat Gaucher's disease, protected against EV71 infection [2].…”
Section: Newer Approachesmentioning
confidence: 99%